Cranial osteology of Bucconidae - Bueno Ladeira, Lílian Marian Coelho Escobar; Höfling, Elizabeth (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
This paper describes the skull osteology of nine species which belong to Monasa, Malacoptila, Chelidoptera, Nonnula, Bucco, Notharchus and Nystalus genera within the family Bucconidae, a Neotropical avian group, traditionally included in the order Piciformes. The skull anatomy was compared to, mainly, among the families Galbulidae, Picidae, Ramphastidae, Capitonidae and Indicatoridae. The bone structures are also described based on the results which can be verified in some common family characteristics; besides that, some outstanding variation among the species studied are also pointed out. The presence of a well-developed posorbital process, as well as evident and slim zigomatic process, among others, are common characteristics of species belonging to the family Bucconidae. It is clearly noticeable that, regarding the temporal depression, lachrymal bone and palate bone structure, the Monasa, Malacoptila, Nonnula and Chelidoptera genera distinguish themselves from the Bucco, Notharchus and Nystalus by following a pattern that separates them in two distinct groups